Layers upon layers: data sharing & reuse challenges in archaeological contexts - Michael Olsson; Olle Sköld; Lisa Andersson (Information Research: An International Electronic Journal)
Introduction. This short paper presents preliminary findings from a study of archaeologist’s information practices relating to data sharing and reuse.